Copper-catalyzed multicomponent reactions for the efficient synthesis of diverse spirotetrahydrocarbazoles - Zhan, Shao-Cong; Fang, Ren-Jie; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2022)
In the presence of copper sulfate, three- or four-component reactions of 2-methylindole, aromatic aldehydes and various cyclic dienophiles in refluxing toluene afforded diverse spirotetrahydrocarbazoles. This reaction is an important development of the Levy reaction by using 2-methylindole to replace ethyl indole-2-acetate and successfully provides facile access to important polysubstituted spiro[carbazole-3,3'-indolines], spiro[carbazole-2,3'-indolines], spiro[carbazole-3,5'-pyrimidines] and spiro[carbazole-3,1'-cycloalkanes] in satisfactory yields and with high diastereoselectivity.
Keywords: Diels–Alder reaction; indole; indolo-2,3-quinodimethane; Levy reaction; tetrahydrocarbazole; spirooxindole